2022
DOI: 10.1039/d2se01373h
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the green coke production when co-processing lipids at a commercial fluid catalytic cracker (FCC): combining isotope 14C and causal discovery analysis

Abstract: Co-processing biogenic feedstocks allows oil refiners to use their infrastructure while reducing the carbon intensity of the fuels they produce. Although policies such as British Columbia and California’s low carbon...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Recently, causal discovery methods, such as the linear non-Gaussian acyclic model (LiNGAM), have been proposed for linear models. 52,53 The statistical causality between descriptors selected by the LASSO model and product compositions will be explored in our future research. In addition, since the data set used in this study was not obtained with statistical analysis in mind, bias in the data is an issue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, causal discovery methods, such as the linear non-Gaussian acyclic model (LiNGAM), have been proposed for linear models. 52,53 The statistical causality between descriptors selected by the LASSO model and product compositions will be explored in our future research. In addition, since the data set used in this study was not obtained with statistical analysis in mind, bias in the data is an issue.…”
Section: Discussionmentioning
confidence: 99%
“…Although we confirmed that descriptors associated with the reactions that have an important role in determining product composition are likely to be selected, the possibility of a pseudocorrelation has not been denied. Recently, causal discovery methods, such as the linear non-Gaussian acyclic model (LiNGAM), have been proposed for linear models. , The statistical causality between descriptors selected by the LASSO model and product compositions will be explored in our future research. In addition, since the data set used in this study was not obtained with statistical analysis in mind, bias in the data is an issue.…”
Section: Discussionmentioning
confidence: 99%